Vertical Targeting of AKT and mTOR as Well as Dual Targeting of AKT and MEK Signaling Is Synergistic in Hepatocellular Carcinoma - Ewald, Florian (J Cancer, 2015)
Hepatocellular carcinoma (HCC) is the sixth most common cancer, and the third most common cause of cancer related death worldwide. The multi-kinase inhibitor Sorafenib represents the only systemic treatment option until today, and results from clinical trials with allosteric mTOR inhibitors were sobering. Since the PI3K/AKT/mTOR and RAF/MEK/ERK signaling pathways are frequently upregulated in HCC, we have analyzed the effects of AKT inhibitor MK-2206, MEK inhibitor AZD6244 (ARRY 142886) and mTOR kinase inhibitor AZD8055, given as single drugs or in combination, on proliferation and apoptosis of three HCC cell lines in vitro. We show that all three inhibitor combinations synergistically inhibit proliferation of the three HCC cell lines, with the strongest synergistic effect observed after vertical inhibition of AKT and mTORC1/2. We demonstrate that AKT kinase activity is restored 24h after blockade of mTORC1/2 by increased phosphorylation of T308, providing a rationale for combined targeting of AKT and mTOR inhibition in HCC. Our data suggest that a combination of inhibitors targeting those respective pathways may be a viable approach for future application in patients with hepatocellular carcinoma.